PEDAGOGI EKOLOGI MENURUT ENSIKLIK LAUDATO SI’ DAN UPAYA MENGHIDUPINYA OLEH KELOMPOK MINAT FRATER PENCINTA ALAM DI KOMUNITAS RITAPIRET - Sina, Petrus; Jewadut, Jean Loustar; Darling, Dominikus Sinyo (Bahasa Indonesia, 2025)
The ecological crisis haunts modern human life. This crisis emerged as a result of human paradigms and exploitative behaviour towards nature. In the face of the ecological crisis, creative and massive ecological pedagogy to enlighten all parties so that it leads to changes in environmentally friendly lifestyles is an urgent need. This article was written to explore the rich meaning of ecological pedagogy in the Encyclical Laudato Si' and reviewing the form of involvement of the Brother Lovers of Nature (Frapala) interest group at St. Peter Interdiocesan Major Seminary in Ritapiret in implementing ecological pedagogy at the level of pastoral practice. Using qualitative research methods, ecological pedagogy in the Encyclical Laudato Si' understood as an effort to save the environment through education, which is not only limited to theory, but continues to the concrete practice of saving the environment. Ecological pedagogy occurs within the family, educational institutions, and community environments. The Frapala interest group in Ritapiret community seeks to live out ecological pedagogy by celebrating ecological liturgical celebrations, carrying out ecological kerygma, and realizing ecological diakonia. Through this involvement, humans become increasingly aware of the nature of the universal community of all created beings, namely that all creation is interconnected and influences each other.